Developing GPU-compliant algorithms for CMS ECAL local reconstruction during LHC Run 3 and Phase 2. Issue 1 (1st February 2023) - Reis, Thomas; ,
Abstract: The higher LHC luminosities foreseen in Run 3 (2022+) and during the Phase 2 of the LHC (2029+), and the consequently larger number of simultaneous proton-proton collisions per event, pose significant challenges for the CMS event reconstruction. In particular maintaining the strict time budget for reconstruction algorithms at the CMS software high level trigger will not be possible considering only the expected increase of processing power from conventional CPUs. Therefore, CMS is investigating the use of heterogeneous architectures, including GPU accelerators, to satisfy the needs of the Phase 2 reconstruction. The local reconstruction algorithm of the CMS electromagnetic calorimeter (ECAL) is among the first to be implemented on heterogeneous platforms for LHC Run 3. This article discusses the necessary changes to the CMS software framework that support the execution of code on accelerators. The current development status of the ECAL local reconstruction algorithm is described and first performance results of GPU enabled code are presented.